Combatting Stunting through Strategic Management: Implications for National Defense Forces in Developing Countries - Nora Leylana (MultiTech Publisher, 2024)
Abstract: This qualitative research investigates the ramifications of stunting prevalence on defense force recruits' physical readiness and cognitive capabilities in developing countries. Utilizing secondary data, the study aims to elucidate the impact of stunting on military personnel and explore the challenges stunted individuals encounter within national defense forces, consequently affecting force effectiveness. Furthermore, the research evaluates strategic interventions to combat stunting and proposes their integration into national defense frameworks. Findings indicate a significant correlation between stunting prevalence and compromised physical readiness among defense force recruits. Stunted individuals exhibit reduced physical fitness, compromised muscle development, and increased susceptibility to illnesses, hindering their readiness for military service. Moreover, the cognitive capabilities of stunted recruits are notably affected, with diminished memory, attention span, and decision-making abilities identified as challenges within defense forces. Strategic interventions encompassing nutrition programs, healthcare initiatives, and education campaigns emerge as effective measures against stunting. The integration of these interventions into national defense frameworks is proposed to enhance force readiness and performance. This research underscores the urgency of addressing stunting within defense forces, emphasizing its pivotal role in optimizing operational efficiency and effectiveness. Keywords: cognitive capabilities, defense forces, physical readiness, strategic interventions, stunting